Representasi Visual Mahasiswa S1 Pendidikan Matematika tentang Fungsi Multivariabel - Muzangwa, Jonatan; Ogbonnaya, Ugorji I. (Edumatica : Jurnal Pendidikan Matematika, 2022)
Representations of mathematical concepts are very important in the teaching and learning of mathematics. Visual representations are used to present mathematical concepts to solve, explore or explain the concepts. The purpose of this study was to examine undergraduate mathematics education students' visual representations of multivariable functions using matching items tasks. The study was qualitative research conducted with 10 second-year undergraduate mathematics education students at a University in Zimbabwe. The students matched the functions of several variables which are represented in symbolic and graphic forms. The result showed that most of the students were able to match the functions with their graphical representations. However, most of the students had difficulties in communicating mathematical information and these difficulties emanate from language problems and conceptual understanding.